Răspuns :
Răspuns:
Explicație pas cu pas:
( x + 3 y)² + ( x - 3 y) ( x + 3 y) = 2 x² + 6 x y
= ( x + 3 y) ( x + 3 y + x - 3 y) = → l-am dat factor comun pe x + 3 y
= ( x + 3 y) × 2 x =
= 2 x² + 6 x y
______________________________________________
Sau:
( x + 3 y)² + ( x - 3 y ) ( x + 3 y ) =
= x² + 6 x y + 9 y² + x² - 9 y² =
= 2 x² + 6 x y
→ aplic formulele:
( a + b)² = a² + 2ab + b²
( x + 3 y)² = x² + 2 × x × 3 y + (3 y)² = x² + 6xy+9y²
______________________________________
( a - b) ( a + b ) = a² - b²
(x - 3y)(x + 3y) = x² - 9y²
(